DDRE-19. PHASE 0/I TRIAL OF MYCOPHENOLATE MOFETIL COMBINED WITH RADIATION TO OVERCOME GLIOBLASTOMA TREATMENT RESISTANCE BY TARGETING DE-NOVO PURINE METABOLISM. (25th March 2021) - Umemura, Yoshie; Sun, Yilun; Junck, Larry; Leung, Denise; Kim, Michelle; Al-Holou, Wajd; Sagher, Oren; Heth, Jason; Lyssiotis, Costas; Marini, Bernard; Lawrence, Theodore; Wahl, Daniel
Abstract: BACKGROUND: Radiation resistance is one of the major limitations for effective control of glioblastoma. Guanosine triphosphate (GTP) supplementation promotes glioblastoma radioresistance. Conversely, GTP depletion overcomes glioblastoma radioresistance by slowing the repair of radiation-induced DNA damage. Mycophenolate mofetil (MMF) inhibits de novo GTP synthesis by inhibiting the key enzyme, inosine-5′-monophosphate dehydrogenase, and radiosensitizes glioblastoma in mice. These pre-clinical findings have led to Phase 0/I Dose Escalation Study of Mycophenolate Mofetil Combined with Radiation Therapy in Recurrent Glioblastoma (NCT04477200) to measure the concentration of active metabolite of MMF in glioblastoma, and to determine the safe dose of MMF when given in combination with radiation. METHODS: Key eligibility criteria are age ≥18, patients with Karnofsky Performance Scale score ≥60, and recurrent glioblastoma or gliosarcoma with clinical indication for re-irradiation (phase I) or re-resection or biopsy (phase 0). Those with tumor involving ≥3 lobes or leptomeningeal space or bevacizumab use within 8 weeks are excluded. Eight participants will receive MMF 500–2000 mg PO BID for one week before surgery (phase 0). Approximately 30 subjects will receive MMF 250–2000 mg PO BID (starting: 1000mg) on TITE-CRM dose escalation model (phase I). RESULTS: From 7/2020 to 11/2020, two phase 0 and three phase I subjects have completed MMF treatment without notable toxicity. Additionally, correlative measurements of the activity of de novo GTP synthesis are explored. The anticipated study duration is 48 months. CONCLUSION: The results of this trial will aid in designing a randomized clinical trial to determine the efficacy of MMF combined with chemoradiation in glioblastoma, and to define potential biomarkers for effectiveness. MMF is widely available and inexpensive, so if positive efficacy result is observed, a brisk acceptance of MMF combined with the standard of care is anticipated.